The Origin, Epidemiology, and Phylodynamics of Human Immunodeficiency Virus Type 1 CRF47_BF - Hill, Gracelyn; Pérez-Losada, Marcos; Delgado, Elena; Benito, Sonia; Montero, Vanessa; Gil, Horacio; Sánchez, Mónica; Cañada-García, Javier E.; García-Bodas, Elena; Crandall, Keith A.; Thomson, Michael M.; , the Spanish Group for the Study of New HIV Diagnoses; et al. (Frontiers in Microbiology, 2022)
CRF47_BF is a circulating recombinant form (CRF) of the human immunodeficiency virus type 1 (HIV-1), the etiological agent of AIDS. CRF47_BF represents one of 19 CRFx_BFs and has a geographic focus in Spain, where it was first identified in 2010. Since its discovery, CRF47_BF has expanded considerably in Spain, predominantly through heterosexual contact (~56% of the infections). Little is known, however, about the origin and diversity of this CRF or its epidemiological correlates, as very few samples have been available so far. This study conducts a phylogenetic analysis with representatives of all CRFx_BF sequence types along with HIV-1 M Group subtypes to place the CRF47_BF sequences in a definitive phylogenetic context. The CRFx_BF sequences cluster into a single, not well supported, clade that includes their dominant parent subtypes (B and F). This clade also includes subtype D and excludes subsubtype F2. The CRF47_BF sequences all share a most recent common ancestor. Further analysis of this clade couples CRF47_BF protease-reverse transcriptase sequences and epidemiological data from an additional 87 samples collected throughout Spain, coupled with additional CRF47_BF database sequences from Brazil and Spain to investigate the origin and phylodynamics of CRF47_BF. The Spanish region with the highest proportion of CRF47_BF samples in the data set was the Basque Country (43.7%) with Navarre next highest at 19.5%. We include in our analysis epidemiological data on host sex, mode of transmission, time of collection, and geographic region. The phylodynamic analysis indicates that CRF47_BF originated in Brazil around 1999-2000 and spread to Spain from Brazil in 2002-2003. The virus spread rapidly throughout Spain with an increase in population size from 2011 to 2015 and leveling off more recently. Three strongly supported clusters associated with Spanish regions (Basque Country, Navarre, and Aragon), together comprising 60.8% of the Spanish samples, were identified, one of which was also associated with transmission among men who have sex with men. The expansion in Spain of CRF47_BF, together with that of other CRFs and subtype variants of South American origin, previously reported, reflects the increasing relationship between the South American and European HIV-1 epidemics.